2017
DOI: 10.1016/j.humpath.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of NRAS is a rare genetic event in ovarian low-grade serous carcinoma

Abstract: Activating mutations involving the members of the RAS signaling pathway, including KRAS, NRAS, and BRAF, have been reported in ovarian low-grade serous carcinoma and its precursor lesion, serous borderline tumor (SBT). Whether additional genetic alterations in the RAS oncogene family accumulate during the progression of serous borderline tumor (SBT) to invasive low grade serous carcinoma (LGSC) remains largely unknown. While mutations of KRAS and BRAF occur at a very early stage of progression, even preceding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
4
13
0
Order By: Relevance
“…We found BRAF mutations in 13.8% (9/65) of LGSC, which falls within the broad range reported previously (2% -33%). 10,[13][14][15]37 This was similar to 17.9% (10/56) reported by Xing et al 37 in a similar sized cohort and slightly higher than AACR GENIE Project database, where the frequency of patients with BRAF mutations in the LGSC was 4/56 (7%, accessed April, 2017). 38 The GENIE Project contains genomic records generated in CLIA-/ISO-certified laboratories obtained at multiple tertiary referral centers 38 , and may be enriched for patients with late stage disease seeking biomarker-driven clinical trials, whereas the patients reported in the current study are prospectively recruited clinic-based cases.…”
Section: Discussionsupporting
confidence: 81%
“…We found BRAF mutations in 13.8% (9/65) of LGSC, which falls within the broad range reported previously (2% -33%). 10,[13][14][15]37 This was similar to 17.9% (10/56) reported by Xing et al 37 in a similar sized cohort and slightly higher than AACR GENIE Project database, where the frequency of patients with BRAF mutations in the LGSC was 4/56 (7%, accessed April, 2017). 38 The GENIE Project contains genomic records generated in CLIA-/ISO-certified laboratories obtained at multiple tertiary referral centers 38 , and may be enriched for patients with late stage disease seeking biomarker-driven clinical trials, whereas the patients reported in the current study are prospectively recruited clinic-based cases.…”
Section: Discussionsupporting
confidence: 81%
“…More recently, NRAS mutations were described in LGSOC. Five studies identified 12 NRAS mutations (either at Q61R or Q61K) in a total of 118 cases, resulting in an average frequency of 9.3% [7], [9], [26], [27], [28]. We found three NRAS mutations in our series.…”
Section: Discussionmentioning
confidence: 46%
“…Xing et al analyzed the NRAS mutation status of SBOTs, noninvasive LGSCs, and invasive LGSCs; interestingly, they did not find a NRAS mutation in either SBOTs or noninvasive LGSCs. According to these authors, the low prevalence of NRAS mutations implies that this gene may play a limited role in the development of LGSC [ 32 ]. However, in the study conducted by Emmanuel et al, activating NRAS mutations were found in 5 out of 58 (9%) invasive serous epithelial ovarian carcinomas coexisting with a serous borderline tumor and in none of the 53 isolated SBOTs.…”
Section: Discussionmentioning
confidence: 99%